tìm x
a. x^5+x^4+1+x=0
b. x^4+3x^3-x-3=0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{2}{3}x\left(x^2-4\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}\frac{2}{3}x=0\\x^2-4=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm2\end{cases}}\)
\(\left(x-y\right)^2\)
\(=\left(x-y\right)\left(x-y\right)\)
\(=\left(x-y\right)x-\left(x-y\right)y\)
\(=\left(x^2-xy\right)-\left(xy-y^2\right)\)
\(=x^2-2xy+y^2\)
Vậy chọ đáp án D. \(x^2-2xy+y^2\)
a, \(\left(\frac{x}{y}-\frac{2}{3}\right)\left(\frac{x}{y}+\frac{2}{3}\right)=\left(\frac{x}{y}\right)^2-\left(\frac{2}{3}\right)^2\)
b,\(\left(2\sqrt{x}-\frac{2}{3}\right)\left(\frac{2}{3}+2\sqrt{x}\right)=\left(2\sqrt{x}-\frac{2}{3}\right)\left(2\sqrt{x}+\frac{2}{3}\right)\)
\(=\left(2\sqrt{x}\right)^2-\left(\frac{2}{3}\right)^2\)
Trả lời:
a, \(\left(\frac{x}{y}-\frac{2}{3}\right)\left(\frac{x}{y}+\frac{2}{3}\right)\)\(=\left(\frac{x}{y}\right)^2-\left(\frac{2}{3}\right)^2=\frac{x^2}{y^2}-\frac{4}{9}\)
b, \(\left(2\sqrt{x}-\frac{2}{3}\right)\left(\frac{2}{3}+2\sqrt{x}\right)=\left(2\sqrt{x}-\frac{2}{3}\right)\left(2\sqrt{x}+\frac{2}{3}\right)=\left(2\sqrt{x}\right)^2-\left(\frac{2}{3}\right)^2=4x-\frac{4}{9}\)
Trả lời:
a, \(\left(3\sqrt{x}-y\right)\left(3\sqrt{x}+y\right)=\left(3\sqrt{x}\right)^2-y^2=9x-y^2\)
b, \(\left(\sqrt{x}-2\sqrt{y}\right)\left(2\sqrt{y}+\sqrt{x}\right)=\left(\sqrt{x}-2\sqrt{y}\right)\left(\sqrt{x}+2\sqrt{y}\right)=\left(\sqrt{x}\right)^2-\left(2\sqrt{y}\right)^2\)
\(=x-4y\)
\(a)\)
\(x^5+x^4+1+x=0\)
\(\Leftrightarrow x^4\left(x+1\right)+\left(x+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x^4+1=0\\x+1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-1\\x^4=-1\text{(Vô lý)}\end{cases}}\)
\(b)\)
\(x^4+3x^3-x-3=0\)
\(\Leftrightarrow x^3\left(x+3\right)-\left(x+3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x+3=0\\x^3-1=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x^3=1\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-3\\x=1\end{cases}}\)
Trả lời:
a, x5 + x4 + 1 + x = 0
<=> ( x5 + x4 ) + ( x + 1 ) = 0
<=> x4 ( x + 1 ) + ( x + 1 ) = 0
<=> ( x4 + 1 ) ( x + 1 ) = 0
<=> x + 1 = 0 ( vì x4 + 1 > 0 )
<=> x = - 1
Vậy x = - 1
b, x4 + 3x3 - x - 3 = 0
<=> ( x4 + 3x3 ) - ( x + 3 ) = 0
<=> x3 ( x + 3 ) - ( x + 3 ) = 0
<=> ( x3 - 1 ) ( x + 3 ) = 0
<=> ( x - 1 ) ( x2 + x + 1 ) ( x + 3 ) = 0
<=> x - 1 = 0 hoặc x + 3 = 0 ( vì x2 + x + 1 > 0 )
<=> x = 1 hoặc x = - 3
Vậy x = 1 hoặc x = - 3